New species and records of Cladiopsocus Roesler (Psocodea: ‘Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia - Obando, Ranulfo González; Aldrete, Alfonso N. García; Carrejo, Nancy (Zootaxa, 2018)
Thirteen species of Cladiopsocus Roesler, from the Colombian departments of Caquetá, Chocó, Magdalena, Nariño, Norte de Santander and Putumayo are here described and illustrated. New records of eight described species of Cladiopsocus, from the departments of Caquetá, Cauca, Quindío and Valle del Cauca are included. The number of species in the genus is increased to 41, of which 27 are Colombian. An updated identification key to the males of the genus is included, as well as a map of species distribution.